STRATEGI MARKETING GUNA MENINGKATKAN KEPUASAN NASABAH PADA PD. BPR BANK JOMBANG (PERSERODA) - Ayuni, Mutiara Elok; Rizqi, Maulidyah Amalina (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
Bank Perkreditan Rakyat (BPR) is one of the banking companies whose business scope is narrower than that of commercial banks. This study aims to identify and analyze PD Strategies. BPR Bank Jombang to build quality banking services to create customer satisfaction for the people in Jombang. This type of research uses a descriptive qualitative research approach, the data collection method used is observation and interview method, the data source used is the primary (direct) data source, namely the interview results, while the data analysis techniques used are triangulation or metode which aims to evaluate how the implementation of strategies to support the success of Bank Jombang's marketing to increase customer satisfaction. From the results of this study, it can be concluded PD. BPR Bank Jombang as a banking company based in the region, that Bank Jombang has a considerable opportunity in developing its business. This can be seen from the achievement of a Simarmas Program that is able to attract customers, and customers are also very enthusiastic in the presence of the Simarmas Program.